The Influence of Social Media, Entrepreneurial Knowledge and Entrepreneurial Motivation on Entrepreneurial Interest in Program Students Entrepreneurship Studies of Malikussaleh University - Nasution, Maylinda; Samsidar, Samsidar; Agustinawati, Agustinawati; Munandar, Munandar (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2024)
This research aims to analyze the influence of social media, entrepreneurial knowledge and entrepreneurial motivation on entrepreneurial interest in students of the Malikussaleh University Entrepreneurship Study Program. Data for this research was collected through a survey method using a questionnaire as a data collection instrument. The population in this study were 110 students from the Malikussaleh University Entrepreneurship Study Program. This research uses a quantitative approach with multiple linear regression analysis using SPSS (Statistical Package for the Social Sciences) software. The results of the research show that partially social media has a positive and significant effect on interest in entrepreneurship among students at the Faculty of Economics and Business, Malikussaleh University. Partially, entrepreneurial knowledge has a positive and significant effect on interest in entrepreneurship among students at the Faculty of Economics and Business, Malikussaleh University. Partially, entrepreneurial motivation has a positive effect. and significant towards interest in entrepreneurship among students at the Faculty of Economics and Business, Malikussaleh University.